2018
DOI: 10.1002/chem.201800142
|View full text |Cite
|
Sign up to set email alerts
|

Tetrylones: An Intriguing Class of Monoatomic Zero‐valent Group 14 Compounds

Abstract: Tetrylones (ylidones) represent a class of zero-valent group 14 compounds with the general formula EL (E=C, Si, Ge, Sn, or Pb; L=neutral σ-donating ligand), wherein the tetrel atom, E(0), possess its four valence electrons in the form of two electron lone pairs, and is moreover coordinated by two ligands (L) via donor-acceptor interactions (L→E←L). This review focuses on the synthesis, structure, reactivity, and computational examination of the isolable heavier tetrylones (Si, Ge, Sn) that have been discovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 61 publications
0
43
0
Order By: Relevance
“…4 . It was found that the overall charges of Ge 9 fragments are −1.6 a.u., while the central Ge-atom bears slightly positive close to zero charge, which were classically found in organogermanium complexes and stabilized by carbine ligands that donate electron pairs into their empty orbitals 35 39 . Thus, the natural population analysis is in a good agreement with our assumption of zerovalent central Ge-atom stabilized by two [Ge 9 ] 2− ligands.…”
Section: Resultsmentioning
confidence: 89%
“…4 . It was found that the overall charges of Ge 9 fragments are −1.6 a.u., while the central Ge-atom bears slightly positive close to zero charge, which were classically found in organogermanium complexes and stabilized by carbine ligands that donate electron pairs into their empty orbitals 35 39 . Thus, the natural population analysis is in a good agreement with our assumption of zerovalent central Ge-atom stabilized by two [Ge 9 ] 2− ligands.…”
Section: Resultsmentioning
confidence: 89%
“…This donor‐acceptor concept is not limited to carbon but applicable to its heavy congeners of Group 14. Several interesting tetrylone systems L→:E:←L (E=Si, Ge, Sn) have thus been developed [10–12] . Since nitrogen(I) is isoelectronic to carbon(0), the donor‐stabilized N I in [L→:N:←L] + , named as nitreones (Scheme 1), [13] has also gained considerable attention [14–16] .…”
Section: Methodsmentioning
confidence: 99%
“…L (E = Si, Ge, Sn) have thus been developed. [10][11][12] Since nitrogen(I) is isoelectronic to carbon(0), the donor-stabilized N I in [L!DND ! L] + , named as nitreones (Scheme 1), [13] has also gained considerable attention.…”
mentioning
confidence: 99%
“…In recent years, low‐valent silicon species have grown in prominence in main group chemistry. Along with greater numbers of and more facile access to known classes of compounds such as silenes and silylenes, new classes such as silylones have also been isolated and investigated. Within this broader area, silyliumylidene ions have emerged as interesting reactive intermediates.…”
Section: Introductionmentioning
confidence: 99%